Evaluation of the beta-glucanolytic enzyme complex of Trichoderma harzianum Rifai for the production of gluco-oligosaccharide fragments by enzymatic hydrolysis of 1,3;1,6-beta-D-glucans - Giese, Ellen Cristine [UNESP]; Monteiro, Alexandre C. [UNESP]; Barbosa, Aneli de Melo; Dekker, Robert F. H.; dos Santos, Osvaldo; Corradi da Silva, Maria de Lourdes; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (World Scientific Publ Co Pte Ltd, 2009)
Botryosphaeran, a new exopolysaccharide from the endophytic fungus Botryosphaeria rhodina MAMB-05, and algal laminarin were hydrolyzed by partially-fractionated enzymes of the beta-glucanolytic complex from Trichoderma harzianum Rifai. beta-Glucanase fractions (F-I and F-II) separated by gel permeation chromatography presented different modes of attack on botryosphaeran and laminarin. Botryosphaeran was hydrolyzed to the extent of 66% (F-I) and 98% (F-II) within 30 min, and its main hydrolysis products were gluco-oligosaccharides of DP >= 4, with lesser amounts of glucose, di- and tri-saccharides. The action of enzyme fractions I and II on laminarin resulted in 15% conversion to glucose, while the percentage of saccharification was radically different (70% for F-I and 25% for F-II). The different product arrays within the polysaccharide hydrolysates can be explained by the difference in the enzymes' specificities within each enzyme fraction, and the molecular structures of the polysaccharides and their complexity.
Keywords: Trichoderma harzianum Rifai; non-cellulosic beta-glucanases; Botryosphaeran; laminarin; Gluco-oligosaccharides